Green Financial Crime Dalam Rezim TPPU Indonesia: Analisis Yuridis Pendekatan Follow The Money - Lukel, Chantikamutiara; Tian Terina (Universitas Pancasakti Tegal, 2026)
This research is motivated by the suboptimal integration between environmental law enforcement and the anti-money laundering (AML) regime in Indonesia, despite the large scale of illicit financial flows generated by environmental crimes. The urgency of this study lies in the need to understand the position of Green Financial Crime (GFC) as a predicate offense and to evaluate the effectiveness of the follow the money approach, which remains rarely examined academically. Employing a normative juridical method enriched with secondary data analysis of Indonesian Financial Intelligence Unit (PPATK) reports and related policy documents, this study reveals two key findings. First, the conceptual construction of GFC in Indonesia is formed through a three-layer interaction: the normative foundation of predicate offenses, the financial intelligence categorization practices by PPATK, and the structural risk mapping within the National Risk Assessment. Second, money laundering typologies from environmental crime not only follow the classical placement–layering–integration pattern but are specifically integrated into natural resource supply chains through the use of front companies, co-mingling practices, and cross-border transactions. These findings confirm that the effectiveness of the follow the money approach remains hindered by the dominance of sectoral enforcement and limited beneficial ownership transparency, thereby necessitating a repositioning of the AML regime as a primary instrument for depriving criminals of illegal profits.